Sigmoid volvulus in pregnancy: Current approach in diagnosis and treatment - Dişçi, Esra; Peksöz, Rıfat; Kara, Salih; Atamanalp, Sabri Selcuk (Journal of Surgery and Medicine, 2022)
Background/Aim: Sigmoid volvulus (SV) is an uncommon disease worldwide, while SV complicating pregnancy is extremely rare. The aim of this study is to evaluate the current diagnostic and therapeutic options in SV during pregnancy in a case series. Methods: The clinical data of 1,046 patients with SV, including 11 pregnant women, were reviewed retrospectively. Age, gestation period, previous history of volvulus, presence of comorbidities, duration of complaints, symptoms, signs, diagnostic tools, treatment procedures and prognosis were noted. Rigid or flexible sigmoidoscopy and magnetic resonance imaging (MRI) were used in the diagnosis, while abdominal X-ray and computerized tomography (CT) were avoided. Stable patients were treated with endoscopic decompression, while emergent surgery was needed in complicated cases with necrosis, peritonitis, or unsuccessful endoscopic decompression. Results: The mean age was 31.0 years (24-39 years). All cases were multiparous. Of the patients, 6 (54.5%) were in third trimester, 4 (36.4%) were in second trimester, and 1 (9.1%) was in first trimester. SV was diagnosed by endoscopy in 6 patients (54.5%), by magnetic resonance imaging (MRI) in 2 (18.2%), and during laparotomy in 3 (27.3%) patients. 6 patients (54.5%) were decompressed by sigmoidoscopy, while 5 cases (45.5%) were treated with surgery. One patient (9.1%) was lost due to toxic shock arising from sigmoid necrosis, while a stillbirth (9.1%) was developed following the surgical procedure in the same case. Conclusion: Although common findings including abdominal pain, obstipation and distention are prominent clinical features of SV, some clinical findings of pregnancy may cloud the pathology during pregnancy. We recommend sigmoidoscopy or MRI in the diagnosis of pregnant patients with suspected SV. Although enlarged uterus is generally thought as an impediment factor for endoscopic decompression, flexible sigmoidoscopy is currently preferred in the treatment of uncomplicated and non-gangrenous patients, while gangrenous or complicated cases are required emergency surgery regardless of the gestation period.